CLINICAL SKILLS INSTRUCTOR’S PERCEPTION OF FEEDBACK EXPERIENCE USING THE PENDLETON METHOD - Ronanarasafa, Ronanarasafa; Claramita, Mora; Suhoyo, Yoyo (Jurnal Pendidikan Kedokteran Indonesia: The Indonesian Journal of Medical Education, 2025)
Background: Feedback at the    Faculty of Medicine, Universitas Islam Al-Azhar is one of the formative assessments given to the students. The feedback given so far is unstructured and tends to emphasize only the negative side. The process of providing feedback needs to be deeply evaluated by using a framework from the Pendleton method. This study aims to evaluate the training in giving feedback using the Pendleton method for clinical skills instructors.Methods:  A mixed-method design was used. The study assessed changes in instructors’ knowledge and application of the Pendleton feedback method, as well as their experience in delivering structured feedback. Knowledge was measured with a pre–posttest questionnaire, while the ability to deliver feedback was assessed using a Likert-scale rating completed by trained observers during feedback sessions. In addition, a focus group discussion (FGD) with four guiding questions was conducted among instructors who had completed the training and implemented the Pendleton feedback method. Qualitative data were analyzed using content analysis.Results: There was a significant improvement in instructors’ knowledge of how to give structured feedback in clinical teaching settings after the Pendleton training. This improvement was also supported by insights from the FGD, which indicated enhanced confidence and clarity in delivering feedback.Conclusion: The Pendleton technique of feedback is effective in improving instructors’ ability to provide structured and constructive feedback in clinical education. This structured approach was perceived by participants as useful for facilitating student learning and enhancing the overall feedback process.